Fabrication of biomimetic vascular scaffolds for 3D tissue constructs using vascular corrosion casts. (1st March 2016) - Huling, Jennifer; Ko, In Kap; Atala, Anthony; Yoo, James J.
Graphical abstract: Abstract: Vascularization is among the most pressing technical challenges facing tissue engineering of 3D organs. While small engineered constructs can rely solely on vascular infiltration and diffusion from host tissues following implantation, larger avascular constructs do not survive long enough for vessel ingrowth to occur. To address this challenge, strategies for pre-vascularization of engineered constructs have been developed. Various biofabrication techniques have been utilized for pre-vascularization, but limitations exist with respect to the size and complexity of the resulting vessels. To this end, we developed a simple and novel fabrication method to create biomimetic microvascular scaffolds using vascular corrosion casting as a template for pre-vascularization of engineered tissue constructs. Gross and electron microscopic analysis demonstrates that polycaprolactone (PCL)-derived kidney vascular corrosion casts are able to capture the architecture of normal renal tissue and can serve as a sacrificial template for the creation of a collagen-based vascular scaffold. Histological analysis demonstrates that the collagen vascular scaffolds are biomimetic in structure and can be perfused, endothelialized, and embedded in hydrogel tissue constructs. Our scaffold creation method is simple, cost effective, and provides a biomimetic, tissue-specific option for pre-vascularization that is broadly applicable in tissue engineering. Statement of Significance: Tissues in the body are vascularized to provide nutrients to the cells within the tissues and carry away waste, but creating tissue engineered constructs with functional vascular networks has been challenging. Current biofabrication techniques can incorporate blood vessel-like structures with straight or simple branching patterns into tissue constructs. Unfortunately, these techniques are expensive, complicated and create simplified versions of the complex vessel structures seen in native tissue. Our technique uses novel vascular corrosion casts of normal tissue as templates to create vascular scaffolds that are a copy of normal vessels. These vascular scaffolds can be easily incorporated into 3D tissue constructs. Our process is simple, inexpensive and inherently tissue-specific, making it widely applicable in the field of tissue engineering.